2022
DOI: 10.1073/pnas.2110415119
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sensor conserved from bacteria to humans

Abstract: Significance Amino acids are the building blocks of life and important signaling molecules. Despite their common structure, no universal mechanism for amino acid recognition by cellular receptors is currently known. We discovered a simple motif, which binds amino acids in various receptor proteins from all major life-forms. In humans, this motif is found in subunits of calcium channels that are implicated in pain and neurodevelopmental disorders. Our findings suggest that γ-aminobutyric acid–derived … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(103 citation statements)
references
References 44 publications
9
94
0
Order By: Relevance
“…Multiple lines of evidence indicate that the capacity to sense and respond to amino acids is of crucial importance for many forms of life. (1) A recent study has identified an amino acid‐specific sensor domain, dCache_1AA, that is found throughout the Tree of Life in archaea, bacteria, and different eukaryotes (Gumerov et al, 2022). In bacteria, this domain is found in all major families of transmembrane receptors, including chemoreceptors, sensor kinases, guanylate/adenylate cyclases, cyclic‐di‐GMP phosphodiesterases or serine/threonine kinases and phosphatases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple lines of evidence indicate that the capacity to sense and respond to amino acids is of crucial importance for many forms of life. (1) A recent study has identified an amino acid‐specific sensor domain, dCache_1AA, that is found throughout the Tree of Life in archaea, bacteria, and different eukaryotes (Gumerov et al, 2022). In bacteria, this domain is found in all major families of transmembrane receptors, including chemoreceptors, sensor kinases, guanylate/adenylate cyclases, cyclic‐di‐GMP phosphodiesterases or serine/threonine kinases and phosphatases.…”
Section: Discussionmentioning
confidence: 99%
“…The PSPTO_2448 chemoreceptor has a dCache_1 LBD domain that contains an amino acid recognition motif conserved in bacteria, archaea, and eukaryotes (Gumerov et al, 2022), suggesting that the perception of amino acids is an important feature throughout the Tree of Life. Considering its conservation and the important role of amino acids as signals for both plants and PsPto, we investigated signal recognition by PSPTO_2448 and its role during plant interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance to our current study, we have recently characterized a single nucleotide mutation in CACNA2D1 , 73 which results in a substitution of Aspartate for Glycine at position 209, which is in the recently identified double Cache domain (dCache1) 29 of α 2 δ-1. This mutation leads to a nonfunctional protein that does not traffic beyond the ER, and is not proteolytically processed into α 2 and δ.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of α 2 δ-1 protein is of importance in the development of neuropathic pain, 24–27 and α 2 δ-1 is also the drug target for gabapentinoid drugs used in neuropathic pain. 28 , 29 These drugs inhibit calcium channel trafficking when applied chronically. 14 , 18 In the present study, we have examined the nature of the enzyme(s) involved in proteolytic cleavage of α 2 δ subunits, since inhibition of its proteolytic cleavage could represent a novel point of therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus proposed for this motif [Y 121 R 126 W 128 Y 129 Y 144 D 173 , numbered according to PctA, Fig. 4A] contains two parts: in the N-terminal part, the residues Y121, R126 and W128 are involved in key contacts with the carboxyl group of the ligand, while the C-terminal part contains Y144 and D173 making contact with the amino group of the ligand [25]. As observed in Fig.…”
Section: The Lbd Of So_1056 Contains Conserved Residues That Could Be...mentioning
confidence: 99%